Non-prise en charge et évidentialité à travers les langues - Tóth, Andrea (Verbum – Analecta Neolatina, 2013)
This paper aims to discuss the values associated with the French epistemic conditional and to give an overview of its discursive functions, as well as of their rendering in the process of translation. Our investigations are based on a journalistic parallel corpus. Our method is contrastive in that wemake remarks as to the extent to which equivalence is reached in the target text with respect to the speaker’s commitment and the diversification of uttering sources.